2013
DOI: 10.4253/wjge.v5.i4.174
|View full text |Cite
|
Sign up to set email alerts
|

Endocytoscopic visualization of squamous cell islands within Barrett’s epithelium

Abstract: AIM:To study the endocytoscopic visualization of squamous cell islands within Barrett's epithelium. METHODS:Endocytoscopy (ECS) has been studied in the surveillance of Barrett's esophagus, with controversial results. In initial studies, however, a soft catheter type endocytoscope was used, while only methylene blue dye was used for the staining of Barrett's mucosa. Integrated type endocytoscopes (GIF-Q260 EC, Olympus Corp, Tokyo, Japan) have been recently developed, with the incorporation of a high-power magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It is tempting to speculate that the use of second-generation EC with a lower magnification at the time of their study could have been a contributing factor which may have potentially affected the results. In 2013, Eleftheriadis et al made a first account describing in-vivo high quality images of squamous cell islands as round-shaped cells with heterogeneouslyshaped small nuclei within regular Barrett's epithelium by using third-generation EC (23). In this study, it was concluded that EC seems to be promising in the evaluation of Barrett's mucosa compared to results from previous studies.…”
Section: Esophageal Ecmentioning
confidence: 73%
“…It is tempting to speculate that the use of second-generation EC with a lower magnification at the time of their study could have been a contributing factor which may have potentially affected the results. In 2013, Eleftheriadis et al made a first account describing in-vivo high quality images of squamous cell islands as round-shaped cells with heterogeneouslyshaped small nuclei within regular Barrett's epithelium by using third-generation EC (23). In this study, it was concluded that EC seems to be promising in the evaluation of Barrett's mucosa compared to results from previous studies.…”
Section: Esophageal Ecmentioning
confidence: 73%
“…Endocytoscopy enables real‐time evaluation of the glandular ductal structures and shapes of the cell nuclei at a precision level that is nearly equivalent to that of histopathological examination. The usefulness of endocytoscopy has been reported for diagnosis of lesions in the esophagus, stomach, and colon, 20–24 and diagnostic criteria have been established, especially for lesions of the esophagus and colon 20,23 . However, only three studies have previously demonstrated the feasibility of endocytoscopy for lesion of the duodenum 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…The endocytoscope, like a conventional magnifying endoscope, only requires operation by a lever and allows in vivo assessment of the histopathological features, including the cell nuclei, in real time. The usefulness of endocytoscopy has been reported for diagnosis of lesions in the esophagus, 20,21 stomach, 22 and colon, 23,24 but only a small number of reports of this technique for lesions of the duodenum have been published, 25–27 and its usefulness is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…12 There are a couple of studies regarding Barret's esophagus. 13,14 Tomizawa proposed a classification system for Barret's esophagus that referred to Inoue's ECA classification. Although it was a pilot ex vivo study, their classification system provided 95.8-98.3% accuracy for esophageal adenocarcinoma.…”
Section: Ec For Esophageal Diseasesmentioning
confidence: 99%